ANALISIS BILINGUALISME DALAM INTERAKSI SOSIAL VANILLA LOVELY (ADIK VALLENE LAURENCIA SELEBGRAM TIKTOK) - Murniasih, Siti; Casim, Casim (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
This study describes the use of bilingualism that occurs in social interactions in children. Specifically, what happened to Vanilla Lovely, the younger sister of Vallene Laurencia, a TikTok celebrity. The purpose of this study was to determine the form of bilingualism and the factors causing bilingualism in Vanilla Lovely's social interactions in videos uploaded via the TikTok account @Vanillaaa_ly. This type of research is qualitative research. The method used in this study is a descriptive method with qualitative analysis. The data collection technique used is the listening and recording technique. The data analysis techniques used in this study are, 1) data collection; 2) data identification; 3) data simplification; and 4) data analysis accompanied by verification. The findings of this study present 5 data obtained from the form of bilingualism in Vanilla Lovely's social interactions, namely: 1) utterance one, "Iya, I want to cake"; 2) utterance two, "Pink" and "Cool, cute"; 3) utterance three, "No, I just dislike chocolate"; 4) utterance four, "Four"; and 5) utterance five, "Tapi aku gak tahu, I can't speak Indonesian that smart". In addition, the factors causing bilingualism are caused by educational factors and family factors. Keywords: Bilingualism, Social Interaction, and Vanilla Lovely.